2015
DOI: 10.1111/rge.12062
|View full text |Cite
|
Sign up to set email alerts
|

Ar–Ar Ages of Hydrothermal Muscovite and Igneous Biotite at the Guposhan–Huashan District, Northeast Guangxi, South China: Implications for Mesozoic WSn Mineralization

Abstract: The Guposhan-Huashan district is an important W-Sn-Sb-Zn-(Cu) metallogenic area in South China. It is located in the middle-west segment of the Nanling Range. Granitoids in the Guposhan-Huashan district possess certain properties of A-type or I-type granites. The W-Sn-Sb-Zn mineralization in the district is closely associated with magma emplacement. Two igneous biotite and seven hydrothermal muscovite samples from skarn, veins and greisenization ores were analyzed by Ar-Ar methods. Two igneous biotite samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…The Guposhan-Huashan Sn-W district is one of the most important districts in the western of the Nanling Sn-W belt (Figure 1C). The Sn-W deposits in this district (e.g., Xinlu Sn-Zn deposit, Shuiyanba Sn deposit, Keda Sn deposit, Huashan Sn deposit, and Shanhu W-Sn deposit) are located at the contact zone of the Guposhan-Huashan granite pluton and its vicinity (Figures 1C, 2A;Feng et al, 2019;Gu et al, 2007a, b;Kang et al, 2012;Li et al, 2016;Xiao et al, 2011;Zhang et al, 2020;Zhao et al, 2010). Considerable uncertainty and controversy remains regarding the exact timing of W-Sn mineralization.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The Guposhan-Huashan Sn-W district is one of the most important districts in the western of the Nanling Sn-W belt (Figure 1C). The Sn-W deposits in this district (e.g., Xinlu Sn-Zn deposit, Shuiyanba Sn deposit, Keda Sn deposit, Huashan Sn deposit, and Shanhu W-Sn deposit) are located at the contact zone of the Guposhan-Huashan granite pluton and its vicinity (Figures 1C, 2A;Feng et al, 2019;Gu et al, 2007a, b;Kang et al, 2012;Li et al, 2016;Xiao et al, 2011;Zhang et al, 2020;Zhao et al, 2010). Considerable uncertainty and controversy remains regarding the exact timing of W-Sn mineralization.…”
Section: Introductionmentioning
confidence: 91%
“…The study area mainly consists of semipelagic flysch sedimentary rocks and subsequently underwent the Early Paleozoic intraplate orogeny. Scattered Mo-W, Pb-Zn, and Au mineralization associated with this orogeny are represented by the Baishiding, Zhanggongling, and Longshui deposits in the eastern of the district (Figure 2A; Li et al, 2016). From Early Devonian to Jurassic, carbonate platforms with sporadic clastic rocks formed in this area under a shore-shallow sea-slope setting (Shu, 2012).…”
Section: Regional Geologymentioning
confidence: 97%
See 1 more Smart Citation
“…The Nanling region is famous for its large-scale and multi-stage magmatism and abundant W, Sn and other rare-metal resources and reserves [2,3,[15][16][17][18][19][20][21][22]. Previous studies have revealed the presence of [2]), showing the distribution of granitic plutons, basalts, and related W-Sn deposits and their geochronological data compiled from [17][18][19]21,29,[31][32][33][34][35][36][37]. TB: Tarim block; CAB: Cathaysian Block; NCB: North China Block; SCB: South China Block; YZB: Yangtze Block.…”
Section: Introductionmentioning
confidence: 99%
“…These precise data provide detailed chronological constraints on the emplacement age of the Xitian pluton and for the time interval between W-Sn mineralization of the Xitian deposit. The majority of these chronological data show that the Xitian pluton could be subdivided into the Late Triassic (Indosinian) granites (230-220 Ma) and the Late Jurassic (Yanshanian) granites (160-140 Ma), and the time interval for W-Sn [2]), showing the distribution of granitic plutons, basalts, and related W-Sn deposits and their geochronological data compiled from [17][18][19]21,29,[31][32][33][34][35][36][37]. TB: Tarim block; CAB: Cathaysian Block; NCB: North China Block; SCB: South China Block; YZB: Yangtze Block.…”
Section: Introductionmentioning
confidence: 99%